Filipino Christ and the Historical Jesus - Asis, Michael Demetrius H (Archīum Ateneo, 2021)
In his project to analyze, discover, and elicit a new socially-relevant Filipino Christ, Dr.Michael Asis appeals to the historical study of Jesus and the development of christology, to the interpretation of the past as relevant to the present, and to an empirical cultural study of Filipino spirituality. People generally relate to Christ who shares in our suffering in this world, but incarnates God’s forgiveness of human weakness. “He died for our sins.” Christ lives deeply inside family values; he is God’s presence celebrated in liturgy, in the feasts and fiestas of the year, and in personal devotion, especially in crisis. But the opening up of Jesus’ actual ministry, so vividly portrayed in the gospel stories, signals for the public sector a new relevance of Christ to moral commitment. This book proposes that a turn to the ministry of Jesus provides a new link between the doctrine of Christ and Philippine society and culture. Asis concretely suggests how the church can help nurture Filipino spirituality, modeled on Jesus’ ministry, into social responsibility and commitment. This penetrating study puts Filipino flesh on a movement that is going on across cultures throughout the world.